Induction of Diabetes Abolishes the Antithrombotic Effect of Clopidogrel in Apolipoprotein E–Deficient Mice - Sugidachi, A.; Ohno, K.; Jakubowski, J. A.; Ito, Y.; Tomizawa, A.; Mizuno, M. (TH Open, 2017)
Patients with acute coronary syndrome with diabetes mellitus (DM) exhibit an impaired platelet inhibitory response to clopidogrel which is only partially understood. DM was induced by the administration of streptozotocin (STZ) to 9-week-old mice. The antithrombotic effects of clopidogrel (10 mg/kg/d, orally × 5 days) were determined using a FeCl3-induced thrombosis model employing wild-type (WT), apolipoprotein E (apoE)-deficient, and diabetic apoE-deficient mice at 21 weeks. Antiplatelet effects were determined using flow cytometry. The antithrombotic effects of clopidogrel were similar in WT and apoE-deficient mice but were attenuated in diabetic apoE-deficient mice with the percent inhibition of thrombus area (µm2) by clopidogrel being 85.5% (WT mice), 75.0% (apoE-deficient mice), and 1.9% (diabetic apoE-deficient mice). The time to first occlusion and lumen stenosis also reflected a significant loss of the antithrombotic effects of clopidogrel in diabetic apoE-deficient mice. Ex vivo platelet activation, which was assessed using ADP-induced expression of activated glycoprotein IIb/IIIa, was completely inhibited by clopidogrel in these three groups of mice. In contrast, the effect of clopidogrel on the ex vivo expression of platelet P-selectin induced by protease-activated receptor 4–activating peptide was diminished in diabetic apoE-deficient mice compared with that in WT and apoE-deficient mice. These data suggest that diabetic apoE-deficient mice may serve as a useful model to better understand the impaired responses to clopidogrel in patients with DM, which may partially reflect a reduction of the effect of clopidogrel on thrombin-induced platelet activation.
Keywords: P2Y12; clopidogrel; diabetes mellitus; platelets; thrombosis; apolipoprotein E–deficient mouse; thrombin